OPTIMALISASI STRATEGI INTEGRASI KELAPA SAWIT - SAPI PADA BADAN USAHA MILIK NEGARA (BUMN) PERKEBUNAN DI INDONESIA (Studi Kasus Pada PT. Perkebunan Nusantara III (Persero) Medan, Sumatera Utara) - Argo, .; Rahardjo, Kusdi; Wicaksono, Karuniawan Puji (Profit: Jurnal Adminsitrasi Bisnis, 2015)
The objectives of this research are to understand the condition of internal and external environment in applying the strategy of integration between palm oil plants and beef cattles on PTPN III (SOEs). This research also provide alternative strategies in order to optimize the strategy of integration between palm oil plants and beef cattles on PTPN III. The determination of strategy in terms of managerial and operational side. This research use the primary data obtained from, observation, interview and by distibuting questionnaries to the respondents. Its also use secondary data obtained from various medias. Analysis tools used are SWOT analysis (manajerial side) and linear programming (operational side). Based on SWOT analysis showed that PTPN III still has weaknesses internally in harnessing the strengths to overcome weaknesses. On other side PTPN III has provided a positive reponse to the opportunities and threats faced. Alternative strategies offered i.e. production costs efficiency, pursuing product development strategy, improve the technical maintenance of beef cattle, maximize production capacity, conducting training and recruiting human resources on animal husbandry sector, maximize the utilization of palm oil plants waste and insuring the assets owned. Based on linear programming analysis the alternative strategies offered are pursuing fattening system if Â ADG development more than or equal to 0,4 kg per day and pursuing breeding system if ADG development less than or equal to 0,3 kg per day.Â Â